Understanding health care avoidance and initial help-seeking behavior in German veterans: a theory of planned behavior - Siegel, Stefan (Psychol Res Behav Manag, 2018)
OBJECTIVE: To gain initial insights into salient beliefs of former German soldiers (veterans) about the use of mental health services. DATA SOURCE: Narrative interviews with former German soldiers (veterans) were conducted in 2016. DATA COLLECTION/EXTRACTION METHOD: Forty-three interviews were transcribed and analyzed thematically based on the theoretical framework of the theory of planned behavior. From within the behavorial, normative, and control beliefs, the salient beliefs were identified. PRINCIPAL FINDINGS: Four groups of salient beliefs were identified, described, and named: “Autarky”, “Ineffectiveness”, “Heteronomy”, and “Incapacity”. CONCLUSION: Interventions and campaigns addressing these four specific groups of beliefs may lead to higher health service use rates. However, as a result of methodological limitations of the study design, the conclusion remains tentative.